Limited functional compensation among subunits of the carbonic anhydrase module of mitochondrial complex I - Nehuen Balestieri; Fernanda Marchetti; Ana Caroline P. Martins; Danilo M. Daloso; Gabriela Pagnussat; Juan Pablo Córdoba; Eduardo Zabaleta (Planta, 2026)

CRISPR/Cas9-mediated disruption of the gamma carbonic anhydrase 2 gene leads to reduced mitochondrial complex I and growth alterations in tomato - Matías Ariel Valiñas; Ignacio Cerrudo; Fernanda Marchetti; Fernando Villarreal; Gabriela Pagnussat; Eduardo Zabaleta (Planta, 2026)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Herpes simplex virus type 2 modulates the susceptibility of human bladder cells to uropathogenic bacteria - Fabiana Superti; Catia Longhi; Assunta Di Biase; Antonella Tinari; Magda Marchetti; Silvia Pisani; Carmela Gallinelli; Fernanda Chiarini; Lucilla Seganti (Medical Microbiology and Immunology, 2001)